Enhancing Fourth Grade Students’ Mathematics Achievement through the Snowball Throwing Model Assisted by the Smart Wheel - Nuraini, Nabila; Hidayat, Puput Wahyu; Andriani, Opi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
Mathematics education in Indonesia continues to face challenges such as low student engagement and achievement in elementary schools, often due to traditional teacher-centered methods. This study implemented the Snowball Throwing model assisted by Smart Wheel media to improve fourth-grade students’ mathematics achievement at SDN 112/II Purwobakti. The research employed Classroom Action Research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected through teacher and student observations, learning outcome tests, and documentation. The study involved 28 students and utilized quantitative and qualitative analysis to evaluate the effectiveness of the intervention. Results and discussion: he research employed Classroom Action Research (CAR) following Kemmis and McTaggart’s framework, conducted in two cycles to achieve measurable improvement within a practical timeframe. Participants were 28 students. Data were gathered through validated observation sheets, achievement tests, and documentation, with reliability ensured through expert review and inter-rater agreement. Quantitative data were analyzed using percentage and gain score calculations, while qualitative data were triangulated from observations and reflections. This study highlights the effectiveness of active learning models combined with interactive media in improving mathematics education. Teachers are encouraged to adopt such innovative strategies, while schools should provide support through training and resources. Future research could explore the model's applicability to other subjects or digital platforms.